ผลของการฝึกจินตภาพที่มีต่อความแม่นยำในกีฬาเปตอง - เดชะ พุมานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of the present study was to investigate the effects of imagery training on the accuracy in la roulette,la portee and le tir petanque techniques. Methods Thirty-four 10-12 years old males from Kehatungsonghongwitaya1 who had experiences in basic petanque were purposively selected to be a subject in this study. The experimental group was trained the petanque skills with imagery training and the control group was trained only the petanque skills. The subjects were tested at before, after 4 weeks and after 8 weeks training by petanque skills and imagery questionaire. The obtained data were analyzed, using independent t-test to test for the differences of the mean between groups and one-way analysis of variance with repeated measures was used to test for the differences of the mean within groups. Results The la portee skills of the experiment group were significantly different than the control group. The la routette skills of the experiment group were significantly better than the control group after eight weeks of the study at the .05 level. But le tir skills of both groups were no significantly at the .05 level.Conclusion The effects of imagery training on the accurancy in petanque in the experiment group, the la roulette skills was better after 8 weeks, the la portee skills was better after 4 and 8 weeks but the le tir skills of both groups were no significantly different. The conclusion is petanque skills with imagery training can develop greater petanque skills.